Microbe Mage - Rosli, Nur Ezzati; Addenan, Nurul Asyiqin; Mohd Nazri, Noor Fatin; Mohd Zakir, Nurhafizah; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
E-learning has become a buzz in the education system and it caters to the needs of modern learners. Microbe Mage is a board game that implements diverseness of e-learning tools, such as website, Aurasma, Quizlet etc, in familiarizing the world of microorganisms in a more interactive environment, instead of conventional way. This game is designed for secondary school and pre-university students so it can be a medium for them to enhance knowledge in microbiology. In short, Microbe Mage makes learning more interesting and stimulating for students, and encourage students to be more IT competent.